2003
DOI: 10.1046/j.1365-2141.2003.04306.x
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic model for survival in chronic lymphocytic leukaemia based on p53 expression

Abstract: Summary. As the abnormal expression of p53 protein is prognostically significant in some human cancers, its significance in patients with B-cell chronic lymphocytic leukaemia (CLL) was assessed. Two investigators evaluated the percentage of bone marrow mononuclear cells that stained for p53, using biopsies stained with anti-p53 monoclonal antibody (DO-7), and graded the degree of staining (0, +, ++, +++). Samples from a cohort of 90 patients with CLL were studied (median age 60 years, range 30-89 years; 57 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Chemoresistance has been attributed to a variety of factors such as high expression of antiapoptotic proteins, loss of functional p53, mitochondrial defects, and, possibly, in vivo exposure to exogenous prosurvival cytokines in the microenvironment. [2][3][4][5][6][7][8][9][10][57][58][59][60][61][62][63][64][65] These observations have prompted rigorous characterization of the molecular and biochemical features of the disease to gain a better understanding of what additional factors impact chemosensitivity and, hopefully, to uncover novel therapeutic targets. Regardless of the specific mechanistic basis, these studies collectively suggest that a high proportion of CLL patients have defects in their mitochondrial apoptotic machinery that are linked to a poor in vivo response to conventional therapeutic anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemoresistance has been attributed to a variety of factors such as high expression of antiapoptotic proteins, loss of functional p53, mitochondrial defects, and, possibly, in vivo exposure to exogenous prosurvival cytokines in the microenvironment. [2][3][4][5][6][7][8][9][10][57][58][59][60][61][62][63][64][65] These observations have prompted rigorous characterization of the molecular and biochemical features of the disease to gain a better understanding of what additional factors impact chemosensitivity and, hopefully, to uncover novel therapeutic targets. Regardless of the specific mechanistic basis, these studies collectively suggest that a high proportion of CLL patients have defects in their mitochondrial apoptotic machinery that are linked to a poor in vivo response to conventional therapeutic anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…Because the loss of p53 (chromosome 17p deletion) is associated with a poor prognosis for disease progression and resistance to therapy, [57][58][59][60] we evaluated whether p53 status affects the sensitivity of CLL cells to BFA. Of the 30 CLL patient samples used in this study, 20 patient samples had cytogenetic analyses for deletion of p53 at chromosome 17p by fluorescent in situ hybridization (FISH) analysis.…”
Section: The Sensitivity Of Cll Cells To Brefeldin a Is Independent Omentioning
confidence: 99%
“…Mechanisms accounting for this deficiency include overexpression of antiapoptotic molecules such as Bcl-2, Mcl-1, and survivin, and impaired expression of proapoptotic molecules including death receptors and p53 (53)(54)(55)(56)(57)(58)(59). Indeed, abnormal p53 expression is predictive of shorter survival in patients with CLL (54,55). Although p53 mutations occur only in a small number of patients with CLL, they present a major clinical problem (60).…”
Section: Discussionmentioning
confidence: 99%
“…13,21 TP53 mutation causes overexpression of the mutated protein and several recent studies have shown that TP53 mutations in solid tumors, lymphomas, and myelodysplastic syndrome can be accurately predicted by immunohistochemistry using widely available antibodies to the p53 protein. 21,23,24 In this study, we sought to determine the prevalence of p53 protein immunoreactivity in bone marrow samples from therapyrelated myeloid neoplasm patients and to evaluate its association with mutations in the TP53 gene. We also sought to assess whether p53 immunoreactivity was associated with patient outcome in two large cohorts of therapy-related myeloid neoplasm patients with clinical follow-up.…”
mentioning
confidence: 99%